PERAN KOMUNIKASI WORD OF MOUTH DALAM PROMOSI PRODUK EMINA - Emnis La Heinzhe; Weni Nurmayanti (Triwikrama: Jurnal Ilmu Sosial, 2025)
This study aims to explore the role of Word of Mouth (WOM) as an effective marketing strategy in promoting Emina products, especially among teenagers. WOM is known as a more authentic approach compared to commercial advertising, especially in the cosmetics industry targeting the teenage market. Recommendations from friends, family, or influencers are considered more credible and influential on consumer purchasing decisions. This study uses a qualitative descriptive method by collecting data through questionnaires and literature studies, and analyzed to describe the impact of WOM on brand image and consumer loyalty. The survey results show that the majority of respondents get information about Emina products through WOM on social media, especially from influencers and friends' reviews. Influencers on social media platforms such as Instagram and TikTok have proven effective in increasing brand awareness and positive consumer perceptions of products. This study also found that WOM plays an important role in building brand loyalty, where satisfied consumers tend to recommend products to others, thereby strengthening the bond between consumers and brands. Thus, WOM, especially through digital platforms, has proven to be a crucial promotional tool for cosmetic brands targeting young consumers. The results of this study provide insights for marketers in designing effective communication strategies to build a strong brand image and increase consumer loyalty.